A tunable bifunctional hollow Co3O4/MO3 (M = Mo, W) mixed-metal oxide nanozyme for sensing H2O2 and screening acetylcholinesterase activity and its inhibitor. Issue 30 (29th June 2020) - Zhang, Xiaodan; Lu, Yuwan; Chen, Qiumeng; Huang, Yuming
Abstract : Mo and W tunable bifunctional hollow Co3 O4 /MO3 mixed-metal oxide nanozymes were fabricated. They exhibit similar O2 activating ability, while their discrepant H2 O2 activating capability is likely ascribed to different catalytic mechanisms. Abstract : A self-templated strategy was adopted to design hollow Co3 O4 /MO3 (M = Mo, W) mixed-metal oxides via the Mo or W doping of ZIF-67, and subsequent pyrolysis under an atmosphere of air at a low temperature of 450 °C. The hollow Co3 O4 /MO3 (M = Mo, W) mixed-metal oxides displayed tunable oxidase-like and peroxidase-like activities able to efficiently catalyze the oxidation of TMB to generate a deep blue color in the absence or presence of H2 O2 . Relative to that of the un-doped Co3 O4, the oxidase mimic activity of the Mo-doped Co3 O4 increased to 1.3 to 2.1-fold, while its peroxidase mimic activity increased to 7.1 to 19.9-fold, depending on different Mo doping amounts. The oxidase mimic activity of the W-doped Co3 O4 increased to 2.1 to 2.3-fold, while its peroxidase mimic activity increased to 4.8 to 5.9-fold, depending on the different W doping amounts. The Mo- and W-doped Co3 O4 nanohybrid exhibited both higher O2 and H2 O2 activating capability, and their H2 O2 activating capacity was superior to the O2 activating capability. Furthermore, the Mo- and W-doped Co3 O4 nanohybrids exhibited similar O2 activating abilities, while the Mo-doped one displayed a higher H2 O2 activating capability than the W-doped one. The discrepant peroxidase-like nature of Mo- and W-doped Co3 O4 nanohybrids is likely attributed to their different catalytic mechanisms. The peroxidase-like activity of Mo-doped Co3 O4 is highly related to the ˙OH free radical, while that of W-doped Co3 O4 is likely ascribed to the electron transfer between TMB and H2 O2 . The K m values of Co3 O4 /MoO3 for TMB and H2 O2 were 0.0352 mM and 0.134 mM, which were 3.2- and 1.9-fold lower than that of pure Co3 O4, respectively. A Co3 O4 /MoO3 -based colorimetric platform was developed for the determination of H2 O2 in the 0.1–200 μM range, with a limit of detection of 0.08 μM (3σ). Based on the thiocholine (TCh) inhibition of the excellent peroxidase-like activity of Co3 O4 /MoO3 and the TCh generation via acetylcholinesterase (AChE) catalyzed hydrolysis of acetylthiocholine chloride (ATCh), the colorimetric platform was extended to screen AChE activity and its inhibitor.